Online Conversion of Tamil Language into Tactile for Visual Impaired People - K.M.R. , Navadeepika; Kumar, Ambeth (International Journal of Psychosocial Rehabilitation, 2020)
To access the materials for visually impaired people, there are various technologies available. One of the most popular materials is the Braille book. To obtain knowledge with the Braille book, the tactile dot technology is used by the blind. The project’s goal is to structure and build up a Braille system and develop the output for visually impaired people that empowers them to collaborate and convey. This examination proposes an algorithm that empowers the user to change over the content that we ordinarily have in our everyday utilization into a Braille script and subsequently encourage the visually disabled.